Characterization of Prototype Formulated Particleboards from Agroindustrial Lignocellulose Biomass Bonded with Chemically Modified Cassava Peel Starch - Stephen Warui Kariuki; Jackson Wachira; Millien Kawira; Genson Murithi Leonard (Advances in Materials Science and Engineering)
Conventional methods of making particleboards utilize wood chips. This has resulted in a decrease in the tree cover due to the increase in wood demand. The effect has been climatic change. Wood is bound using phenol formaldehyde resin. Because of the decrease in the forest cover, alternative lignocellulose materials are required. In this study, lignocellulose materials used include sugarcane bagasse, maize stock, and rice husks. The cassava-starch mix with borax was used as a binder in particleboard formulation. The lignin content was determined, and its effect on properties of boards was investigated. The resultant composite material was molded at a pressure of 6.5 N/mm2 and at 30°C. The resultant particleboards had mean densities ranging from 0.604 to 0.611 g/cm3. The modulus of elasticity ranged from 2364.2 N/mm2 to 3329.93 N/mm2, modulus of rupture ranged from 13.55 N/mm2 to 14.83 N/mm2, and internal bonding ranged from 1.613 N/mm2 to 2.370 N/mm2. The performance of the board was dependent on the lignocellulose material used. Fourier transform infrared spectroscopy analysis showed that main chemical bonding in the particleboard resulted from esterification of –COOH from lignocellulose and OH- from starch. The particleboards formulated were found to be of low-density-fibre standard used in a similar manner to the conventional low-density particleboards.